William Alwyn the art of film music - Johnson, Ian 1940- (Boydell, 2023)
Ian Johnson's evaluation of Alwyn's film music places his achievement in the context of wider movements within the film industry. William Alwyn was a leading composer of British film music in the 1940s and '50s, a time when the British film industry was at its peak. His scores ranged from documentaries to almost 80 full-length feature films, including classics such as Fires were Started, Desert Victory, Odd Man Out, The Fallen Idol, and The History of Mr Polly; he was adept at any musical genre, from classical to cartoon slapstick, and in the process worked with legendary directors, including Carol Reed, David Lean, Humphrey Jennings, and Anthony Asquith. Alone with Vaughan Williams he was granted the distinction of a separate title credit; columnists mentioned him alongside Bliss, Bax and Walton. However, as the reputation of the British film industry declined in the 1950s, so musical snobbery against those who were its leading lights became unpleasantly raw. In recent years, however, with sensitive performances of hisfilm and concert music available on CD, this most appealing of composers has enjoyed something of a renaissance. In this long overdue reassessment, Alwyn's films are analysed and put into the context of his biography,the film industry, and of society at large: the author shows in particular this remarkably versatile composer developed a hitherto unrecognised grammar of film music which enhanced every film on which he worked. He also examines his work for war propaganda, radio, and the concert hall. The volume is enhanced by the most complete filmography, discography, and bibliography of the composer's works yet published, as well as listings of his concert and radio music